Pembuatan Buku Komik Panduan Perpustakaan di Perpustakaan Daerah Kota Padang Panjang - Nuskhalisyah, Cahyana; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThe paper describes how to make the library guide comic book. As media toincrease students visit interest at Padang Panjang city library. The objective of this paper is to describe the way to make the library guide comic book. Data collection of this paper is based on exploring the comic library guide book, library obsevation, guide book. According to the explanation, the steps of how to make the library guide comic book  are: (1) prepare the tools and materials(2) Find the ideas and concepts(3) state the story theme(4) the story plot (5)write the story manuscript(6) draw comic sketch(7) create comic’s characters(8) match characters body language and facial expression(9) draw conversation baloons and comic’s text(10) define story endings(11) make comic book’s cover(12) keep the result of drawing. After the previous steps are finished, comic books can print and used and read.Keywords: Comic, Guedebook, Library, and Student.